Post-weaning growth and blood parameters of milk replacer fed and naturally suckled Black Bengal kids - Moniruzzaman, M; Afroz, S; Khatun, A; Alam, MH; Islam , MN; Amin, MR (Bangladesh Journal of Animal Science, 2022)
The present study was carried out to know the effect of feeding soybean-based milk replacer on post-weaning growth and blood parameters of milk replacer-fed and naturally suckled goat kids. Twenty four Black Bengal kids were allocated into two groups; treatment group (n=12, 6 male and 6 female) was reared artificially with milk replacer, and control group (n=12, 6 male and 6 female) was kept with their dam for natural suckling. Milk replacer was prepared with powdered milk and soybean powder (1:1). After weaning, the live weight of kids was recorded weekly. The blood samples were collected from the kids to determine haematological parameters. The live weight did not differ significantly between artificially fed and naturally suckled male and female kids. Wither height and heart girth showed significantly (p<0.05) higher in the milk replacer fed male kids than naturally reared males. Body length of female kids was significantly (p<0.05) higher in milk replacer fed group than naturally suckled group. Heart girth and red blood cell (RBC) were found significantly (p<0.05) higher in artificially fed kids than naturally reared both male and female kids. Therefore, it can be concluded that artificial feeding with milk replacer can be an alternative way of kid rearing under farm conditions. Bang. J. Anim. Sci. 2021. 50 (2): 86-91